The Effect of Investment Motivation, Financial Literation, and Financial Behavior on Investment Decisions (Studies on Management Students at Pelita Bangsa University) - Nataliana Bebasari; Anis Istikomah (Kusuma Negara Business School, 2020)
This study aims to examine the effect of investment motivation, financial literacy and financial behavior on investment decisions. This type of research is quantitative research using descriptive methods. Processed data is primary data obtained from the results of distributing questionnaires with simple random sampling technique to students majoring in management at Pelita Bangsa University. From 7179 students, a sample of 380 respondents was obtained. Data analysis was performed using the PLS (Partial Least Square) program. The results of this study indicate a positive and significant effect of investment motivation, financial literacy and financial behavior on investment decisions.